The teacher evaluation handbook : step-by-step techniques and forms for improving instruction - Manning, Renfro C. (Englewood Cliffs, N.J. : Prentice Hall, 1988)
This book is about: Evaluation-Growth or harassment; Training evaluators; The evaluation instrument as a basis for staff development; ...
Keywords: Education; Teachers; United States; Teachers -- Rating of -- United States -- Handbooks, manuals, etc